Definition of the term “ultimate beneficial owner” within the scope of European anti money laundering legislation and sanctions legislation currently applicable in the European Union on the Russian Federation - Priede, Diāna (Riga Graduate School of Law, 2023)
The term “beneficial owner” plays a critical role within the compliance area in the European Union- both Anti Money Laundering and Sanctions. Thus the author is aiming to research what is the definition of the term “ultimate beneficial owner” within the scope of European Anti Money Laundering legislation and Sanctions legislation currently applicable in the European Union. The author has put forward an aim of identification of the characteristics that the term is assigned within the two legal fields- Anti Money Laundering Legislation and Sanctions against Russian Federation implementing legislation. The objectives of the research are: 1) Research the development of the sanctions throughout the history and research the definitions of the term “sanctions”, in particularly- “targeted sanctions” 2) Study the introduction of the term beneficial owner and its following development within the European Union Anti Money Laundering Legislation. 3) Analyse the term beneficial owner within the European Union sanctions imposing legislation developed against the Russian Federation. 4) Explore whether the term has common characteristics within the two legal fields. Despite the fact that the two legal fields are perceiving different aims if the terminology is to be aligned and complementary the practical implementation of such would be simplified and be more efficient.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Financial law; Anti-money laundering; Beneficial owner; Targeted sanctions; The European Union; Russian Federation